Nematode community responses to range‐expanding and native plant communities in original and new range soils. Issue 20 (2nd October 2018) - Wilschut, Rutger A.; Kostenko, Olga; Koorem, Kadri; van der Putten, Wim H.
Abstract: Many plant species expand their range to higher latitudes in response to climate change. However, it is poorly understood how biotic interactions in the new range differ from interactions in the original range. Here, in a mesocosm experiment, we analyze nematode community responses in original and new range soils to plant communities with either (a) species native in both the original and new range, (b) range‐expanding species related to these natives (related range expanders), or (c) range expanders without native congeneric species in the new range (unrelated range expanders). We hypothesized that nematode community shifts between ranges are strongest for unrelated range expanders and minimal for plant species that are native in both ranges. As a part of these community shifts, we hypothesized that range expanders, but not natives, would accumulate fewer root‐feeding nematodes in their new range compared to their original range. Analyses of responses of nematodes from both original and new ranges and comparison between range expanders with and without close relatives have not been made before. Our study reveals that none of the plant communities experienced evident nematode community shifts between the original and new range. However, in soils from the new range, root‐feeding nematode communities of natives and related range expanders were more similar than in soils from the original range, whereas the nematode community of unrelated range expanders was distinct from the communities of natives and related range expanders in soils from both ranges. The abundances of root‐feeding nematodes were comparable between the original and new range for all plant communities. Unexpectedly, unrelated range expanders overall accumulated most root‐feeding nematodes, whereas related range expanders accumulated fewest. We conclude that nematode communities associated with native and range‐expanding plant species differ between the original and the new range, but that range‐expanding plant species do not accumulate fewer root‐feeding nematodes in their new than in their original range. Abstract : We tested whether communities of climate change‐driven range‐expanding plant species accumulate different communities of nematodes in soils from their new range compared to soils from their original range. We examined plant communities that either consisted of range expanders with or range expanders without relatives in the native community, and the nematode responses to these native relatives were also examined. We did not find clear shifts in nematode community composition between original and new range soils, but found distinct responses to plant community type.